Implementation of Religious Education in the Constitution of the Republic of Indonesia - Syarifah Gustiawati Mukri; Ahmad Mukri Aji; Nur Rohim Yunus (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
Abstract:The regulation of the education system in Indonesia is contained in the constitution of the Indonesian republic. Communities are given the right to education and teaching that is fair and equitable. In addition, the state is also obliged to educate the lives of the Indonesian people, as stated in the opening of the Constitution of the Unitary State of the Republic of Indonesia, even becoming the ideals of the Indonesian nation after its independence.Keywords: Education, Constitution, Rights of citizens Abstrak: Pengaturan tentang sistem pendidikan di Indonesia termaktub dalam konstitusi republik Indonesia. Masyarakat diberikan hak untuk mendapatkan pendidikan dan pengajaran yang adil dan merata. Selain itu, negara juga berkewajiban untuk mencerdaskan kehidupan masyarakat Indonesia, sebagaimana tertuang dalam pembukaaan Undang-Undang Dasar Negara Kesatuan Republik Indonesia, bahkan menjadi cita-cita bangsa Indonesia pasca kemerdekaannya. Kata Kunci: Pendidikan, Konstitusi, Hak warga Negara